Biogeography of the Neotropical genus Malacoptila (Aves: Bucconidae): the influence of the Andean orogeny, Amazonian drainage evolution and palaeoclimate. (2nd November 2016) - Ferreira, Mateus; Aleixo, Alexandre; Ribas, Camila Cherem; Santos, Marcos Pérsio Dantas
Abstract: Aim: To uncover geographical and temporal patterns of diversification in the puffbird genus Malacoptila, focusing on the influence of landscape and palaeoclimate evolution as drivers of diversification. Location: Neotropical, with an emphasis on the Amazon basin. Methods: We sequenced eight mtDNA and nuclear gene regions of 176 individuals belonging to seven of the eight recognized Malacoptila species. Concatenated and time calibrated coalescent multi‐locus phylogenies, along with a Bayesian species delimitation analysis, were performed for the genus. Phylogeographical and historical demography patterns were reconstructed for the Amazonian species. Ancestral ranges estimation was performed in BioGeoBEARS. Results: Our analysis recovered 23 reciprocally monophyletic lineages within Malacoptila . All currently recognized species were recovered as monophyletic. With the exception of M. semicincta, all species presented some level of intraspecific phylogeographical structure, varying up to 10 reciprocally monophyletic phylogroups ( M. rufa ). The distributions of these lineages are generally coincident with known Neotropical areas of endemism (AE). Main Conclusion: Our results corroborate the influence of Andean uplift and the Plio‐Pleistocene establishment of the current drainage system in Amazonia as likely drivers of diversification. The spatially structured genetic diversity that exists within Malacoptila is underestimated by current taxonomy and provides another example of widespread cryptic avian endemism in the Neotropics.